Influence of Arab Spring (2011) on Lebanon political life (Journal of Oriental Studies, 2017)
In the article is considered the impact of Arab Spring 2011 on the political life of Livan. It is analyzed the ethno-confessional system and the internal political situation in the country and the role of the party “Hezbollah”.